Effect of Preoperative Vitamin D Deficiency on Hypocalcemia in Patients with Acute Hypoparathyroidism after Thyroidectomy - Peeradon Vibhatavata; Pongthep Pisarnturakit; Mongkol Boonsripitayanon; Paveena Pithuksurachai; Nattachet Plengvidhya; Sirinart Sirinvaravong (International Journal of Endocrinology)
Postoperative hypoparathyroidism is a common complication of total or completion thyroidectomy. The association between preoperative vitamin D deficiency (VDD) and the development of more severe postoperative hypocalcemia is still unclear. Objectives. To evaluate the effect of preoperative VDD on severity of hypocalcemia in patients with hypoparathyroidism following thyroidectomy. Methods. Patients who developed acute hypoparathyroidism after total or completion thyroidectomy, defined as postoperative parathyroid hormone (PTH) level <15 pg/mL and albumin-adjusted calcium level <8.6 mg/dL, were prospectively recruited. Patients were divided into two groups according to their preoperative vitamin D status (VDD group: 25-hydroxyvitamin D (25(OH)D) level <20 ng/mL; non-VDD group: 25(OH) level ≥20 ng/mL). The primary outcome was severity of hypocalcemia in postoperative hypoparathyroidism. Significant hypocalcemia was defined as calcium level ≤7.5 mg/dL. Results. Forty-three patients (21 VDD, 22 non-VDD) were enrolled. Serum total albumin-adjusted calcium level was significantly lower in the VDD group (7.71 ± 0.5 vs. 8.16 ± 0.4 mg/dL, p<0.01), and the incidence of symptomatic hypocalcemia was significantly higher in the VDD group (43% vs. 9%, p=0.01). The median maximal daily supplementary dose of elemental calcium was significantly higher in the VDD group (2,400 vs. 1,500 mg/day, p=0.02). Length of hospital stay was nonsignificantly longer in the VDD group (p=0.06). Preoperative vitamin D level <19.6 ng/mL could predict significant and symptomatic hypocalcemia in postoperative hypoparathyroidism with sensitivity of 90% and 82% and specificity of 70% and 69%, respectively. Conclusion. VDD is an independent risk factor for both significant and symptomatic hypocalcemia in hypoparathyroidism patients after thyroid surgery.